Laboring Towards New Privacy Protections in the Workplace - Jairo R. Villalobos (Washington University Journal of Law and Policy, 2022)
Employers undoubtedly have an interest in monitoring workplace activity to gather information. However, the rapid development of new technology and subsequent erosion of technological constraints on employee monitoring has magnified the invasiveness of employer surveillance activities. Coupled with a decline in labor union membership throughout the country and mobilization of the workforce, these changes have made it much more difficult for employees to object to unfair and abusive privacy practices by their employer. This Note analyzes the shortcomings of the existing privacy protections for employees and the ways in which big data analytics allow employers to circumvent existing privacy protections and harm employee privacy interests. Villalobos argues that more rigorous protections of employee data are needed. By examining the existing legal privacy landscape in the employment context, Villalobos proposes a general framework for thinking about federal privacy legislation through a fictitious Federal Privacy Law that protects the privacy rights of employees and all Americans. Villalobos argues this proposal will best serve the interests of employees who have been left unprotected by existing privacy laws.
Keywords: Employee Monitoring; Employee Surveillance; Privacy; Privacy Protections for Employees; Big Data; Analytics